Evaluation Of The Implementation Of The Utilization Of The E-Health Center Application At The Periuk District Health Center, Tangerang City - Siti Nurdinillah (Sean Institute, 2024)
The latest regulation from the Indonesian Ministry of Health stipulates that all health service facilities must organize Electronic Medical Records (EMR). This encourages health centers to apply e-Health Center for the real-time data input process based on the Circular issued by the Tangerang City Health Office. However, based on service monitoring, it is known that not all health centers have achieved the set real-time input target. This study aims to evaluate the utilization of the E-Health Center application in four selected health centers, namely Gembor, Periuk Jaya, Kedaung Wetan, and Cipadu in 2024. The study used a qualitative study design by conducting in-depth interviews, document reviews, and observations of opinions and conditions of the use of the e-Health Center application. The Contextual, Input, Process, and Product (CIPP) process framework and the Edward III implementation framework (bureaucratic structure, resources, disposition, and communication) were used to evaluate the implementation. The study involved 4 persons in charge, 5 users, and 2 decision makers of the information system at the health center. The results of the study show that contextually the e-Puskesmas application only meets the utilization objectives based on the Minister of Health's regulation on electronic medical records. The utilization of e-Puskesmas has not created a digital work culture that accelerates and facilitates the work of health workers and minimizes paper use. This is because the input and process of utilizing e-Puskesmas still have obstacles and do not conform to the expected standards. This study recommends improving the utilization of e-Puskesmas with adequate BLUD budget support and the preparation of uniform standard procedures across all health centers.